Evaluation of Cost-Benefit and Measures During the COVID-19 Pandemic for Incoming Travelers Through Tests in Origin in Spain - Domínguez, Conrado; García, Rubén; Sánchez, Javier; Suárez, José Pablo; Dávila-Quintana, Carmen Delia (Frontiers in Public Health, 2022)
Testing strategies for COVID-19 facilitates the overall public health response to the pandemic and contributes to minimizing the infection among the population COVID-19. In this work we assess the efficiency of diagnostic testing of incoming travelers in the Canary Islands, Spain. We study the economic impact, cost-benefit, of this measure as well as the potential influence on the number of positive cases in the population. Results show that testing to income travelers financed by the government may save money for the public health system and study under which scenarios the cost-benefit is given.